Education On The Use Of Long-Term And Permanent Contraception (MKJP) In Watas Marga Village - Monica Yolanda Pandiangan; Eva Marwati; Rizki Apriyani; Kristina Demsia Simaremare; Suwi Hartati; Ronalen Situmorang; Kintan Annisa (Universitas Dehasen Bengkulu, 2026)
The low utilization of Long-Term and Permanent Contraceptive Methods (MKJP) is a challenge in rural areas, contributing to high unmet need for family planning and unplanned pregnancies. This community service program aims to increase women's knowledge and acceptance of MKJP through targeted health education in Watas Marga Village. The activity involved 30 women of childbearing age and included counseling, demonstrations of contraceptive models, group discussions, and individual consultations. Results showed an increased understanding of the benefits of MKJP, particularly regarding its effectiveness, safety, and ease of use. Participants also reported reduced fear and misconceptions, and demonstrated a stronger intention to use MKJP. This program demonstrates that community-based education can effectively increase participation in family planning programs and support the achievement of reproductive health goals at the village level.